When populism meets nationalism Reflections on Parties in Power - Martinelli, Alberto (Pubblicazioni ISPI, 2018)
"In Europe and beyond, today populism is alive and kicking. Over the past few years, anti-establishment parties have made substantial strides. Some of them have reached the levers of governments, while others are consolidating their gains. Being a "thin" ideology, populism is being contaminated by nationalism. This book offers a number of case studies on those countries whose governments have been labelled "national-populist". Ranging from Italy to the United States, from the Visegrad countries to Turkey, Russia, and Latin America, this Report aims to single out what all these cases have in common, but also what sets them apart from each other."